2021
DOI: 10.1002/med.21870
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin as a potent anticancer stem cell agent: State of the art and future directions

Abstract: Cancer stem cells (CSCs) are a small subpopulation of cells within a tumor that can both self-renew and differentiate into other cell types forming the heterogeneous tumor bulk. Since CSCs are involved in all aspects of cancer development, including tumor initiation, cell proliferation, metastatic dissemination, therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 227 publications
0
16
0
Order By: Relevance
“…Furthermore, salinomycin and the other ionophores are known to kill cancer stem cells through different mechanisms, which include the modulation of signaling pathways, the initiation of autophagy, mitochondrial dysfunction, oxidative stress, and apoptosis [ 39 ]. Thus, it is possible that one or more of these mechanisms might also be involved in the observed anti- Leishmania activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, salinomycin and the other ionophores are known to kill cancer stem cells through different mechanisms, which include the modulation of signaling pathways, the initiation of autophagy, mitochondrial dysfunction, oxidative stress, and apoptosis [ 39 ]. Thus, it is possible that one or more of these mechanisms might also be involved in the observed anti- Leishmania activity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various anti-CSC natural compounds screened, salinomycin isolated from Streptomyces albicans has proven to be a perfect candidate for killing CSCs. 103 Basu et al developed lipid nanocapsules (LNCs) coloaded with PTX and salinomycin, which showed superior drug loading capacity and storage stability. Its lipid properties facilitate efficient cellular uptake, delivering drugs to breast cancer cells and CSCs simultaneously.…”
Section: Npns Targeting Cscsmentioning
confidence: 99%
“…However, these limitations can get overruled by investigating targeted delivery approaches or synthesizing their more specific and less toxic analogs. Recent research has reported the successful utilization of nanomicelles, nanoparticles, nanotubes, and cell surface markers (CD133 and CD44) conjugated multilamellar liposomes for targeted and efficient delivery of salinomycin [ 83 , 84 , 85 , 86 , 87 ].…”
Section: Natural Polyether Ionophores Antibiotics As Potent Anticance...mentioning
confidence: 99%